2005
DOI: 10.1063/1.1853520
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism of anomalous shift and asymmetric hysteresis behavior of ferroelectric thin films

Abstract: We studied theoretically the hysteresis behavior of ferroelectric thin films. The anomalous ferroelectric response is discussed by use of a bilayer model. Electrical conductivities of the films have been taken into account. To model the effects of the inhomogeneity of polarization and permittivity across the interface, the film is assumed to possess a secondary dielectric/ferroelectric phase ͑a dead or passive layer͒ with asymmetric conductivity. This configuration is found to produce large shifting ͑along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 22 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…This phenomenon has been explained by introducing a dead layer interface between the electrode and bulk film, [23][24][25] in which the shift effect has a dynamic accumulation process of an internal direct-current (DC) electric field; that is, the shift degree of the hysteresis loop should depend on time development. 25 Under an applied electric field of 450 kV/cm, the 2P r of the BNTZ thin films with various Zr contents (x = 0, 0.05, 0.1, 0.3, and 0.5) were 31 lC/cm 2 , 35 lC/cm 2 , 46 lC/cm 2 , 28 lC/cm 2 , and 26 lC/cm 2 , respectively. These 2P r values demonstrate that Ti-site substitution by Zr could enhance the 2P r value of BNT thin film.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been explained by introducing a dead layer interface between the electrode and bulk film, [23][24][25] in which the shift effect has a dynamic accumulation process of an internal direct-current (DC) electric field; that is, the shift degree of the hysteresis loop should depend on time development. 25 Under an applied electric field of 450 kV/cm, the 2P r of the BNTZ thin films with various Zr contents (x = 0, 0.05, 0.1, 0.3, and 0.5) were 31 lC/cm 2 , 35 lC/cm 2 , 46 lC/cm 2 , 28 lC/cm 2 , and 26 lC/cm 2 , respectively. These 2P r values demonstrate that Ti-site substitution by Zr could enhance the 2P r value of BNT thin film.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Grossmann and co-workers proposed that a strong electric field within a weak-ferroelectric or nonferroelectric surface layer can drive the voltage shift, 12 and with a single surface layer Wong and Shin have theoretically modeled the shifted and deformed P-E hysteresis loops. 13 Although the origin of such a layer is still under debate, Abe et al 14 have attributed it to an asymmetrical relaxation of the epitaxial lattice-misfit strain between BaTiO 3 and the SrRuO 3 bottom electrode, and we also showed that an enlarged misfit can increase the voltage shift in epitaxial Pb͑Zr 0.52 Ti 0.48 ͒O 3 ͑PZT͒ capacitors. 15 This strain-related scenario seems consistent with the imprint induced by mechanical stress, where a simultaneous backswitching of ferroelectric domains, as revealed by the local piezoresponse method, was observed during the polarization reversal.…”
mentioning
confidence: 88%
“…The electrical behaviors of FeFET determine the information storage capability and stability, and they are affected by various degradation effects, such as fatigue, relaxation, and imprint [2]. To understand these mechanisms, a lot of models based on mathematical function, such as the Miller model [3], Preisach model [4], Lue model [5], and Zheng model [6], were proposed to simulate hysteresis behavior and degradation effect of ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%